Effect of Cucumber Juice on Blood Pressure in Hypertensive Patients in Kongkomos Village: Pengaruh Pemberian Jus Mentimun Terhadap Tekanan Darah pada Penderita Hipertensi Di Desa Kongkomos - Andi Herman; Sesisyana Sesisyana (Salando Health Journal, 2024)
Hypertension is one of the major health problems that increases the risk of cardiovascular disease and premature death. This study aims to measure the effect of cucumber juice administration on blood pressure in hypertensive patients in Kongkomos Village. This study used a quasi-experimental design with a pre-test and post-test approach without a control group, involving 30 respondents who were selected by purposive sampling. Respondents were given 200 ml of cucumber juice every morning for seven days, and blood pressure was measured before and after the intervention. The results of the study showed a statistically significant and clinically significant decrease in blood pressure. The mean systolic blood pressure decreased from 150 mmHg to 135 mmHg, and diastolic blood pressure decreased from 95 mmHg to 85 mmHg, with a value of p = 0.000 (p < 0.05). Reductions of 15 mmHg (systolic) and 10 mmHg (diastolic) are clinically relevant as they reduce the risk of cardiovascular complications such as stroke and heart attack by 20–30%, based on current hypertension management guidelines. Most respondents also reported additional benefits, such as feeling fresher and increased frequency of urination, which indicated the natural diuretic effects of cucumbers, in the absence of serious side effects. This study shows that cucumber juice is effective as a safe, inexpensive, and easy-to-implement non-pharmacological intervention in hypertension management, especially at the community level.